Interaksi Antara Guru dan Siswa dalam Pembelajaran Menggunakan Bahasa Melayu Riau Dialek Kampar di SMP Negeri 1 Kuok Kabupaten Kampar - Yonghwa, Lee; Asriwandari, Hesti; Sofro, Rd. Siti (GERAM (Gerakan Aktif Menulis), 2025)
The process of giving and receiving information will run smoothly if the individuals involved use a language they understand well. The Kampar dialect of Riau Malay, as the mother tongue, is a language closely associated with the lives of teachers and students in Kampar Regency, unlike Indonesian, which seems formal and is rarely used in everyday communication. This study aims to analyse symbolic interactionism in the use of the Kampar dialect of Riau Malay. This study uses a qualitative approach with a case study method. This research was conducted at SMP Negeri 1 Kuok, with the research subjects consisting of 12 teachers and 15 students. The data obtained came from primary and secondary sources. The research data was collected using observation, interviews, and documentation techniques. The results of this study show that the use of the Kampar dialect of Riau Malay in teacher-student interactions is interpreted as a means of communication that creates a friendly, relaxed, and participatory learning atmosphere. This is in line with symbolic interactionism theory, which states that language is not only a tool for conveying messages, but also a social and cultural symbol that strengthens the identity and relationships between its speakers.